The Problem of Enforcing Court Judgments in the Context of Defending the Right to a Fair Trial - BIELOVA, Olena; ROMANENKO, Yevgeniy; KAYDASHEV, Roman (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The proposed paper analyzes in detail the Code of Administrative Procedure as amended by the Law of Ukraine №2147-VIII of 03.10.2017 and other regulatory legal acts concerning enforcing court judgments as to their compliance with the requirements of the Convention for the Protection of Human Rights and Fundamental Freedoms of 1950. Attention is given to the issues, which, in the opinion of the authors and despite the recent changes in procedural legislation, have gone unaddressed, namely the problem of enforcing court judgments in cases of holding a regulatory legal act unlawful and invalid; the problem of judicial control over execution of court judgments in administrative cases; the problem of executing court judgments in cases of allocation, computation and recalculation of funds performed in accordance with the Budget Code of Ukraine; the problem associated with execution of court judgments as to allocating, recalculating, resuming and making payments prescribed by the Law ‘On Compulsory State Pension Insurance’ and, in conclusion, the problem of politicizing a decision to redistribute the budget expenditures in order to execute court judgments. The authors suggested ways of solving the above outlined challenging issues, as well as set forward specific proposals as to needed changes in the current rules of substantive and procedural law.